نحو تحقيق سكن ميسر لفئة الشباب في الجمهورية اليمنية – دراسة حالة مدينة صنعاء - الخزان، يحي محمد; الكباب، عبدالعزيز احمد (University of Science and Technology, Yemen, 2015)
Caring about youth issues has become a global phenomenon for they are the current partners and the future quotes. Moreover, their roles are essential and distinguished in supporting and backing the orientations and developments of communities. Besides, they provide and interact with the comprehensive development process in various fields. So, the trend towards coping with youth issues is one of the critical cases which needs to be comprehensively solved. Establishing affordable housing for Yemini youth is a fundamental issue which is no longer local or regional phenomenon, but it has become an international phenomenon. It was found less burdensome in developed countries than in developing countries. Moreover, one of the complicated problems facing youth is how they can get houses which meet their aspirations, hopes and suit their economic status and their ability to pay. Over the past decades, Republic of Yemen has witnessed a rapid urbanization and a dramatic change in the growth of towns and villages. This change was accompanied by an enormous shortage in housing along with rapid population growth, and a demand increase with a supply decrease during housing experiences which were almost limited. As a result, youth as a very significant part of the society have been ignored. The objective of this research is to study reality and problems of establishing affordable housing for Yemeni youth. Moreover, it aims to propose an appropriate mechanism towards achieving a suitable and secured housing for this class of people based on the following: - An analytical study for the targeted group related to their housing. - A study for the factors influencing the establishment of affordable housing for youth. - To provide a strategy towards facilitating housing for Yemeni youth. - To reach findings and recommendations